2022
DOI: 10.1111/jbi.14496
|View full text |Cite
|
Sign up to set email alerts
|

The importance of considering the evolutionary history of polyploids when assessing climatic niche evolution

Abstract: Aim Although whole‐genome duplication (WGD) is an important speciation force, we still lack a consensus on the role of niche differentiation in polyploid evolution. In addition, the role of genome doubling per se vs. later divergence on polyploid niche evolution remains obscure. One reason for this might be that the intraspecific genetic structure of polyploid complexes and interploidy gene flow is often neglected in ecological studies. Here, we aim to investigate to which extent these evolutionary processes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…We excluded polyploids, such as C 4 samples from clade IIIb (which together with IIIa form clade III), given that polyploidy has been shown to affect population success in different ways (e.g. Monnahan et al ., 2019; Padilla‐García et al ., 2023) and might confound our results. Briefly, these samples were collected during field trips between 2012 and 2019.…”
Section: Methodsmentioning
confidence: 85%
“…We excluded polyploids, such as C 4 samples from clade IIIb (which together with IIIa form clade III), given that polyploidy has been shown to affect population success in different ways (e.g. Monnahan et al ., 2019; Padilla‐García et al ., 2023) and might confound our results. Briefly, these samples were collected during field trips between 2012 and 2019.…”
Section: Methodsmentioning
confidence: 85%
“…A common garden for the purpose of the visitor experiment was established in Průhonice, Czech Republic (49°59'41.042''N, 14°33'55.27''E). This common garden has a similar climate to the original location of the A. arenosa populations (central Europe), and tetraploid A. arenosa grows naturally within a few kilometers of this common garden (Padilla‐García et al 2023). Therefore, we did not expect major changes in the insect visitor community between the common garden and the original locations of the A. arenosa populations, even though we were unable to exclude it.…”
Section: Methodsmentioning
confidence: 99%
“…To decouple the effects of polyploidy from the effect of genetic distance among independent origins in natural systems, common garden or in situ experiments that make within-lineage contrasts between diploids and their neopolyploid progeny are necessary. For observations in natural populations, we might find that controlling for genetic structure and multiple polyploid origins will allow us to detect overarching patterns, for example, as Padilla-García et al (2023) found in a study of niche divergence in Arabidopsis arenosa. There are also other factors that could obscure patterns such as the effects of evolution after WGD, divergent local adaptation across sites, or unpredictable genetic changes that arise across polyploid origins.…”
Section: Challengesmentioning
confidence: 99%
“…Second, there is a growing need to place studies of the evolutionary ecology of polyploids into a phylogenetic and population genetic context. We have known for a long time that polyploid lineages arise recurrently within species (Soltis and Soltis 1999) yet despite this recognition, few studies control for the genetic history of polyploid lineages (Padilla‐García et al 2023). This is necessary because independent polyploid origins may have different genetic backgrounds, traits, and will follow independent evolutionary trajectories.…”
Section: Emerging Frontiersmentioning
confidence: 99%